Use of a Motorlance to Deliver Emergency Medical Services; a Prospective Cross Sectional Study - Apiratwarakul, Korakot; Ienghong, Kamonwon; Mitsungnern, Thapanawong; Kotruchin, Praew; Phungoen, Pariwat; Bhudhisawasdi, Vajarabhongsa (Archives of Academic Emergency Medicine, 2019)
Introduction: Access time to patients with critical or emergent situations outside the hospital is a critical factor that affects both severity of injury and survival. This study aimed to compare the access time to the scene of an emergency situation between a traditional ambulance and motorlance. Methods: This prospective cross sectional study was conducted on all users of emergency call, Srinagarind Hospital, Thailand, from June to December 2018, who received a registration number from the command center. Results: 504 emergency-service operations were examined over a six-month period, 252 (50%) of which were carried out by motorlance. The mean activation time for motorlance and ambulance were 0.57 ± 0.22 minutes and 1.11 ± 0.18 minutes, respectively (p<0.001). Mean response time for motorlance was significantly lower (5.57 ± 1.21 versus 7.29 ± 1.32 minutes; p < 0.001). The response times during 6 a.m. to 6 p.m. were 5.26 ± 1.11 minutes for motorlance and 7.15 ± 1.39 minutes for ambulance (p < 0.001). These measures for night time (6 p.m. to 6 a.m.) were 5.58 ± 1.21 minutes and 8.01 ± 1.30 minutes, respectively (p < 0.001). The mean automated external defibrillator (AED) waiting time for motorlance and ambulance were 5.26 ± 2.36 minutes and 9.24 ± 3.30 minutes, respectively (p = 0.012). The survival rate of patients after AED use in motorlance and ambulance was 80% versus 37.5%; p<0.001. Conclusion: Emergency service delivery by motorlance had lower mean activation time, response time, AED time, and mortality rate of cardiac arrest patients compared to ambulance. It seems that motorlance could be considered as an effective and applicable device in emergency medical service delivery, especially in crowded cities with heavy traffic.